Carotid endarterectomy for symptomatic carotid artery stenosis in a patient who presented with psychosis. Issue 4 (4th April 2022) - Hassanin, Ahmed; Ramsamaroo, Zachary; Barry, Mary; Cassidy, Tim
Abstract : Acute psychosis is an unusual presentation of stroke particularly in a patient with no history of psychiatric illness. We report a case where an elderly male patient with self-inflicted injuries caused by acute psychosis. The investigation confirmed an acute left hemispherical stroke associated with a high-grade left internal carotid artery stenosis. The patient underwent a successful left carotid endarterectomy. His psychotic symptoms resolved and he was discharged home without the need for neuroleptic medication.